Flexible-Lean Processes Optimization: A Case Study in Stone Sector - Silva, Agostinho (2021)
During the downturn in demand in Engineering and Construction Architecture (AEC) activities registered in 2007, the Cluster of Mineral Resources of Portugal (CPMR) put into practice an initiative to boost the Ornamental Stone sector, based on incorporating lean thinking concepts, combined with techniques and technologies to make production processes more flexible. This was called the leanstone hornbook (LH). Since then, the LH has been adopted by several Portuguese Ornamental Stone (OS) companies. For these companies, using the LH means changing their operations to a new model based on (i) their participation in R&D consortium projects, (ii) incorporating the resulting innovations, and (iii) combining innovation with lean thinking. Based on a convenience sample of OS companies, the objective of this research was to assess the economic-financial impact of leanstone operations on Portuguese OS companies. Through a methodological framework based on Key Performance Indicators (KPI) and Innovation Outcomes (IO), indexed to companies’ economic-financial performance, LH was found to generate a potentially positive impact in terms of sales volume, exports, investment capacity and net result